Optimizing Poultry Growth and Meat Quality: Effects of Guanidinoacetic Acid Supplementation in Yellow-Feathered Broilers - Jian Xiao; Lifen Wang; Yuguang Chen; Kai Xiao (Veterinary Sciences, 2025)
This study investigated the effects of dietary guanidinoacetic acid (GAA) supplementation on growth performance, carcass traits, meat quality, intestinal morphology, and cecal microbiota composition in yellow-feathered broilers. A total of 360 one-day-old chicks were randomly assigned to five groups with diets containing 0 (control), 300 mg/kg, 600 mg/kg, 900 mg/kg, and 1200 mg/kg GAA. In the initial growth phase, GAA supplementation increased average daily gain (ADG) by 13.01%, 8.97%, and 12.95% for the 300, 600, and 900 mg/kg groups, respectively, and reduced the feed conversion ratio (FCR), though these changes were not statistically significant (p > 0.05). Higher GAA dosages (900 and 1200 mg/kg) improved post-slaughter pH levels in breast muscle, indicating better meat quality, and significantly enhanced intestinal barrier function by increasing villus height and the villus-to-crypt ratio. However, 1200 mg/kg GAA led to a significant increase in serum ALT levels, raising concerns about potential liver stress. Overall, 900 mg/kg GAA supplementation demonstrated the most beneficial effects across various parameters, suggesting it as an optimal dosage to enhance production performance and meat quality in yellow-feathered broilers. Future studies are encouraged to investigate its long-term safety and underlying mechanisms.